Preparation and characterization of model catalysts: from ultrahigh vacuum to in situ conditions at the atomic dimension - Libuda, Jörg; et al. (Journal of Catalysis, 2003)
In situ characterization and reaction studies of working catalytic systems are an issue of current interest. We present studies on well characterized model systems, i.e., deposited metal nanoparticles, applying a variety of experimental techniques in an attempt to bridge gaps between surface science and catalysis. In particular, we investigate methanol dehydrogenation and ethene hydrogenation under UHV as well as ambient conditions and apply nonlinear optical techniques. We use electron spin resonance to study intermediately formed radicals in Ziegler-Natta polymerization of ethene. It is concluded that there is a chance to transfer results from studies on model systems toward an understanding of catalysis. © 2003 Elsevier Science (USA). All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.prepar
Keywords: Electron spin resonance; Ethene hydrogenation; Ethene polymerization; In-situ studies; Methanol dehydrogenation; Model catalysts; Sum frequency generation